Qur'anic Ethics and Domestic Morality: The Indonesian Ministry of Religious Affairs' Exegesis and Contemporary Family Resilience - Siti Kanzun Najah Wassurur; Siti Asiah; Muhyidin Azmi (Lembaga Yasin AlSys, 2026)
Amid growing concerns over divorce and domestic violence in Indonesia, reconstructing an applicable Qur’anic ethical framework for family life has become an urgent socio-religious imperative. This study examined how the Indonesian Ministry of Religious Affairs’ exegesis, Tafsir Kemenag, reformulates household morality and connects textual hermeneutics with contemporary family resilience. A qualitative library-research design was employed, integrating thematic exegesis (tafsīr mawḍūʿī) with textual discourse analysis. The analysis focused on three normative scriptural loci: Qur’an 23:8, 4:21, and 30:21. The findings indicate that Tafsir Kemenag constructs a foundational triad of domestic ethics comprising mutual trust and relational responsibility, the sacred transcendental covenant of mīthāqan ghalīẓan, and the dynamic psycho-spiritual equilibrium of sakīnah, mawaddah, and raḥmah. Through a contextual, moderate, and maqāṣidī orientation, this state-authorized exegesis rejects patriarchal justifications for domestic violence, denies theological legitimacy to abusive marital conduct, and reinterprets qawwāmah from unilateral authority into a relational ethic grounded in mutual service (khidmah) and shared domestic deliberation (tashāwur). The findings further demonstrate how this ethical interpretation is translated into institutional and cultural practices through official premarital Marriage Guidance (Bimwin) modules delivered by local Offices of Religious Affairs and the popular mnemonic practice of Tepuk Sakinah. The study concludes that Qur’anic domestic ethics can contribute to family resilience when textual interpretation is connected with relational responsibility, nonviolence, reciprocal care, and practical social education. It thereby bridges theoretical exegesis and the sociological application of family-resilience values within Indonesia’s living Qur’an context.